Model-Driven Development and Operation of Multi-Cloud Applications The MODAClouds Approach - Di Nitto, Elisabetta; Matthews, Peter; Petcu, Dana.; Solberg, Arnor; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is open access under a CC BY 4.0 license.
Introduction -- Cloud Service Offer Selection -- The MODAClouds Model-Driven Development -- QoS Assessment and SLA Management -- Monitoring in a Multi-Cloud Environment -- Load Balancing for Multi-Cloud -- Fault-tolerant Off-line Data Migration: The Hegira4Clouds Approach. -Deployment of Cloud Supporting Services -- Models@Runtime for Continuous Design and Deployment -- Cloud Patterns -- Modelio Project Management Server Constellation -- BPM in the Cloud: The BOC Case -- Healthcare Application -- Operation Control Interfaces -- Conclusion and Future Research.
Keywords: Telecommunication; Computer networks .; Software engineering; Computational intelligence; Communications Engineering, Networks; Computer Communication Networks; Software Engineering; Computational Intelligence